A review on phase change material application in building - Cui, Yaping; Xie, Jingchao; Liu, Jiaping; Wang, Jianping; Chen, Shuqin (Advances in mechanical engineering, 2017)
In the past several decades, many literatures have emerged on the topic of phase change material and latent heat storage techniques used in building. Accordingly, it is essential to review previous work to know about phase change material application in building better. This article presents a review on phase change material application situations in building, and several aspects are discussed: phase change material major applications in building, phase change material application areas, phase change material application types, phase change material thermal–physical properties, and phase change material application effects. The results of this research show that phase change material application areas are mainly concentrated into four parts of north latitude from 25° to 60° and south latitude from 25° to 40°. No matter in which region, the use of paraffin is the broadest (the maximum use frequency is up to 87.5%). For organic phase change material, the melting temperature and the heat of fusion vary from 19°C to 29°C and from 120 kJ/kg to 280 kJ/kg, respectively. The best phase change material application effect found is a reduction of 4.2°C for air temperature in room. This study has important and directive significance for the practical application of phase change material in building.